2023
DOI: 10.1002/cepa.2459
|View full text |Cite
|
Sign up to set email alerts
|

The FAILNOMORE project – Practice‐oriented design recommendations against progressive collapse in steel and steel‐concrete buildings

Jean‐François Demonceau,
Tudor Golea,
Ahmed Elghazouli
et al.

Abstract: Structural robustness is a specific safety consideration which is currently addressed in modern codes and standards, including the Eurocodes. It requires particular care from all professionals involved in the construction industry. The need for practical guidelines to mitigate the risk of progressive collapse has been emphasised by recent catastrophic events such as the 9/11 terrorist attack in New‐York. The lack of consistent design rules for practitioners is however clearly identified in existing normative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 7 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…The "alternative load path method" is mainly used to examine the behaviour of structures further to the loss of a column. Experimental and numerical studies have demonstrated that, upon the removal of a column, the structural response is typically characterised by three distinct phases [8], [10] in which the structure passes through: normal exploitation conditions (Phase 1), development of a yielding mechanism (Phase 2) and development of significant deformations and displacements (Phase 3) [11] (see §2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "alternative load path method" is mainly used to examine the behaviour of structures further to the loss of a column. Experimental and numerical studies have demonstrated that, upon the removal of a column, the structural response is typically characterised by three distinct phases [8], [10] in which the structure passes through: normal exploitation conditions (Phase 1), development of a yielding mechanism (Phase 2) and development of significant deformations and displacements (Phase 3) [11] (see §2).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, difficulties related to the accurate characterisation of joints' behaviour are yet to be addressed. Additionally, as highlighted in [4], the quantification of the resistance in Phase 3 may be redundant under specific circumstances associated to the activation of resisting mechanisms capable of arresting the collapse in Phase 2 prior to the onset of catenary stage.…”
Section: Introductionmentioning
confidence: 99%
“…The "indirect" robustness (and progressive collapse resistance) resulting from seismic design is however limited to the members of the lateral load resisting system. When the local damage affects elements of the gravity-load resisting system, which are generally connected using shear connections, the damage may propagate and ultimately lead to disproportionate collapse [3]. The consideration of progressive collapse in a non-seismic part of the structure, or in a non-seismic resistant structure may therefore involve the use of connections with flexural capacity (partial or full).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a significant contribution of the concrete floor slabs to the structural robustness. When the slabs are adequately connected to the steel beams, so developing a composite action, they have a positive benefit (beam mechanism / arching effect / catenary effect) [3], also reducing the local demands in beam-tocolumn connections. When properly proportioned, the slab-beam interaction and level of continuity at beam-tocolumn connections (flexural, axial) can enhance the overall performance of the structure and increase the progressive collapse resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation